Advanced Hyperspectral Analysis of Sediment Core Samples from the Chew Bahir Basin, Ethiopian Rift, in the Spectral Range from 0.25 to 17 µm: Support for Climate Proxy Interpretation - Arnold, Gabriele E.; Foerster, Verena; Trauth, Martin H.; Lamb, Henry; Schaebitz, Frank; Asrat, Asfawossen; Szczech, Claudia; Günter, Christina (Frontiers in Earth Science, 2021)
Establishing robust environmental proxies at newly investigated terrestrial sedimentary archives is a challenge, because straightforward climate reconstructions can be hampered by the complex relationship between climate parameters and sediment composition, proxy preservation or (in)sufficient sample material. We present a minimally invasive hyperspectral bidirectional reflectance analysis in the wavelength range from 0.25 to 17 µm on 35 lacustrine sediment core samples from the Chew Bahir Basin, southern Ethiopia for climate proxy studies. We identified and used absorption bands at 2.2 μm (Al-OH), at 2.3 μm (Mg-OH), at 1.16 μm (analcime), and at 3.98 μm (calcite) for quantitative spectral analysis. The band depth ratios at 2.3 μm/2.2 μm in the spectra correlate with variations in the potassium content of the sediment samples, which also reflect periods of increased Al-to-Mg substitution in clay minerals during drier climatic episodes. During these episodes of drier conditions, absorption bands diagnostic of the presence of analcime and calcite support this interpretation, with analcime indicating the driest conditions. These results could be compared to qualitative analysis of other characteristic spectral properties in the spectral range between 0.25 and 17 µm. The results of the hyperspectral measurements complement previous sedimentological and geochemical analyses, allowing us in particular to resolve more finely the processes of weathering in the catchment and low-temperature authigenic processes in the sediment. This enables us to better understand environmental changes in the habitat of early humans.